Water-solid triboelectric nanogenerators: An alternative means for harvesting hydropower - Jiang, Dongyue; Xu, Minyi; Dong, Ming; Guo, Fei; Liu, Xiaohua; Chen, Guijun; Wang, Zhong Lin (Renewable & sustainable energy reviews, 2019)
Hydropower is an important renewable resource, and is derived from the energy of falling, fast-running, and/or oscillating motions of water, including rainfall, tidal currents, waves, and river flows. Over the centuries, the kinetic energy of hydropower has generally been harvested for either replacing labour directly, or for generating power with electromagnetic generators (EMG). However, it is possible to ignore another important energy source contained in water: the triboelectric energy. Following the first report of water-solid triboelectric nanogenerators (TENG), several types of interesting systems have been studied for harvesting the hydropower from rainfall, tides, waves, river flows, etc. TENG devices provide power differently from EMGs; EMGs generate electricity by a Lorenz force-driven electron flow, whereas TENG devices produce power by asymmetric screening of triboelectric charges in the form of displacement current. With this mechanism, power generation is achieved using water contact and separation motions with the TENG devices. In addition, the output performance of a water-solid TENG device is different from that of EMGs in terms of current, voltage, and frequency. The present study comprehensively reviews water-solid TENG devices for hydropower harvesting. This review first addresses the formation of tribo-charges on a solid surface, followed by the configuration, working principles, and parameters affecting the output performance, as well as applications for energy harvesting and self-powered sensors and actuators. Finally, this study provides an outlook of potential opportunities and challenges. •This study reviews an alternative way for harvesting the hydro energy.•Types of hydro energy sources are comprehensively reviewed.•The reviewed techniques are summarized and suggestion for future study is raised.